Gadamer’s Gorgias: The Imperative of Self-Refutation - Hutchens, Benjamin (Labyrinth, 2022)
Gadamer has written several powerful studies of Platonic dialectic. His emphasis on shared understanding, the fusing of horizons and other hermeneutic notions are partially drawn from a study of Plato’s elenctic dialogues. However, Socrates in Gorgias makes a claim about the imperative of self-refutation that not only complicates our understanding of Socratic method, but Gadamer’s reading of it as well. This article is meant to explore just how the imperative of self-refutation causes difficulty for Gadamer’s understanding of dialectic, especially his distinction between authentic and inauthentic dialectic. After considering the nature of ‘refutation’, this article will examine whether Gadamer’s notions of shared understanding, the ‘facts of the matter’, and self-understanding help us to resolve this problem. It shall be concluded that the teacher must take any refutations of his/her own views seriously, but has no special obligation to refute (introspectively) any of their own views, even those beliefs, theories, principles or criteria that enable him to guide the argument.